Investigating the relationships between race, cardiovascular disease, mild cognitive impairment, Alzheimer's disease, and functional outcomes among older former National Football League players. (31st December 2021) - Brett, Benjamin L; Campbell, Hope; Aggarwal, Neelum T; Kerr, Zachary Y; Chandran, Avinash; Walton, Samuel; Mannix, Rebekah; DeFreese, JD; Echemendia, Ruben J; Guskiewicz, Kevin M; Meehan, William P; McCrea, Michael A
Abstract: Background: Higher prevalence rates of Alzheimer's disease and Related Dementias (ADRD) and cardiovascular disease (CVD) have been reported among former National Football League (NFL) players. Ethnoracial minorities comprise a large proportion of NFL players; among the general population, they experience higher rates of CVD. Ethnoracial minority group membership and CVD are independent risk factors for ADRD. We investigated the associations of race and CVD on risk of AD, mild cognitive impairment (MCI), and functional difficulties in older former NFL players. Method: Former NFL players (N=944; 656 self‐identified as White [69.5%]), aged 50‐92 years (M=64.8+ 8.9)completed a general health survey involving comprehensive health history and current function. CVD included the presence of at least one of the following: coronary artery disease or/myocardial infarction, peripheral vascular disease, and/or stroke. Logistic models assessed individual and interaction effects of CVD and race on odds of MCI and AD; covariates included age, education, and concussion history. A multivariate regression (additional covariate of current psychosocial stressors [Life Events Scale]) examined associations between race and CVD on current function (Patient Reported Outcome Measurement Information System [PROMIS] Depression, Cognitive Function, and Ability to Participate in Social Roles and Activities). Results: CVD (AdjOR=1.73[1.17‐2.55]) and Race (non‐White participants; AdjOR=2.16[1.52‐3.07]) were significantly associated with higher odds of MCI diagnosis. Race (AdjOR=2.90[1.44‐5.83]), not CVD, significantly predicted AD diagnosis. Significant race by CVD interactions were not observed for either MCI or AD. Race (non‐White) was significantly associated with greater depression symptoms (ηp 2 =.022), subjective cognitive difficulties (ηp 2 =.017), and social roles/activity disruptions (ηp 2 =.019). The presence of CVD was associated with greater depression symptoms (ηp 2 =.016) and social roles/activity disruptions (ηp 2 =.011). A significant race by CVD interaction was observed, suggesting that the presence of CVD was disproportionately associated with significantly greater depression symptoms (ηp 2 =.010), subjective cognitive difficulties (ηp 2 =.004), social activity/roles disruption (ηp 2 =.005) among non‐White individuals. Conclusion: Similar to the general population, race and CVD are uniquely and dynamically associated with MCI, AD, and functional difficulties among former NFL players, independent of concussion history. Future work should investigate social determinants of health contributing to racial disparities of long‐term outcomes within this sample.